Unbecoming Men: The Masculinity Crisis of the Bollywood Hero. Issue 3 (4th May 2022) - Jha, Sonal
Abstract: Throughout the history of popular Hindi cinema, the figure of the hero has been identifiable as the bearer of hegemonic masculinity, but in the last five years, this figure appears to have developed an existential crisis with respect to his masculinity. This article seeks to identify why the spotlight has shifted to non-dominant constructions of masculinity. It charts out the changing discourse of masculinity within Bollywood. It also places this in the context of a global masculinity crisis, while attempting to understand the changes within the Indian context propelling the crisis. Three recent popular movies, showcasing narratives of men struggling with issues such as alopecia, sexual dysfunction and a lack of agency, are discussed. The analysis of the male figure probes into why these specific deficiencies become shorthand to question the protagonist's manliness, while also placing him in relation to women and other men around him who serve to accentuate his crisis.